THE THE EFFECT OF REPUTATION AND COMPETENCE ON CUSTOMER LOYALTY THROUGH CUSTOMER TRUST - Dwi Astono , Ari (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2021)
This study aims to analyze the effect of reputation, competence on customer loyalty with customer trust as an intervening variable. The population in this study were students of private tertiary institutions in Central Java who are members of Services for Higher Education Institutions Region VI, while a sample of 5 private universities, using the purposive sampling method, was taken with the Slovin formula of 190 respondents. The analysis technique uses regression analysis. Research results show the customer trust variable can be an intervening variable or able to mediate between the direct influence of the reputation variable and the competency variable on customer loyalty variables.